Where do young men want to access STI screening? A stratified random probability sample survey of young men in Great Britain. Issue 6 (17th April 2012) - Saunders, John M; Mercer, Catherine H; Sutcliffe, Lorna J; Hart, Graham J; Cassell, Jackie; Estcourt, Claudia S
Abstract : Objectives: Rates of sexually transmitted infections (STIs) in UK young people remain high in men and women. However, the National Chlamydia Screening Programme has had limited success in reaching men. The authors explored the acceptability of various medical, recreational and sports venues as settings to access self-collected testing kits for STIs and HIV among men in the general population and those who participate in sport. Methods: A stratified random probability survey of 411 (weighted n=632) men in Great Britain aged 18–35 years using computer-assisted personal and self-interviews. Results: Young men engaged well with healthcare with 93.5% registered with, and 75.3% having seen, a general practitioner in the last year. 28.7% and 19.8% had previously screened for STIs and HIV, respectively. Willingness to access self-collected tests for STIs (85.1%) and HIV (86.9%) was high. The most acceptable pick-up points for testing kits were general practice 79.9%, GUM 66.8% and pharmacy 65.4%. There was a low acceptability of sport venues as pick-up points in men as a whole (11.7%), but this was greater among those who participated in sport (53.9%). Conclusions: Healthcare settings were the most acceptable places for accessing STI and HIV self-testing kits. Although young men frequently access general practice, currently little STI screening occurs in this setting. There is considerable potential to screen large numbers of men and find high rates of infection through screening in general practice. While non-clinical settings are acceptable to a minority of men, more research is needed to understand how these venues could be used most effectively.